STRONG TRUST PRINCIPLE FOR SETTING AUTHOR ROYALTIES ON THE COPYRIGHT OF THE BOOK: Prinsip Kepercayaan yang Kuat untuk Menetapkan Royalti Penulis Tentang Hak Cipta Buku - Maharrani , Siti; Al’am, Rakhmad Su’ad; Simanjuntak, Taufik Hidayat; Rustika, Andri; Reswadi; Dewi, D. K. (Ganec Swara, 2025)
The author of the book as the creator of the intellectual property rights must get a fair reward if the author of the book transfers his exclusive rights to the book publisher to publish and commercialize his creation. Royalty payments to book authors are mandatory for book publishers if both parties have agreed on a licensing agreement. This research aims to examine how copyright law protects authors’ royalties on book copyright on the basis of trust. It provides a further basis for an agreed royalty system, efforts to protect the author’s royalty system, and the protection of book copyright by copyright laws. The research method used is normative with a legislative and conceptual approach. The results of the study show that for book publishing and royalty payments, publishers have used several systems, one of which is a broken royalty system or a system for purchasing book manuscripts at a certain price, a modified royalty system for books, a royalty system based on sponsorships, and a royalty system based on the results of large demand for books. Publishers choose a simple approach to protect the authors’ royalty system from the law, which is by building trust with each other, publishers and authors take care of each other’s rights.